KEEFEKTIFAN MISOPROSTOL PERORAL SEBAGAI PEMATANGAN SERVIKS PADA KETUBAN PECAH DINI KEHAMILAN ATERM DENGAN SKOR BISHOP ≤ 4 DI PADANG - Serudji, Joserizal; Erkadius, Erkadius (Andalas Obstetrics And Gynecology Journal, 2018)
Premature rupture of membranes (PROM) is defined as rupture of membranes before contraction (his). PROM is the case of 5-10% of all deliveries. 70% of cases of PROM occur in term pregnancies. So that PROM in aterm pregnancies is suggested to induce labor to reduce the incidence risk of mother and fetus complications. This study aimed to compare the effectiveness of cervical ripening by using Misoprostol 25 µg peroral and without using Misoprostol 25 µg at term premature rupture of the membrane with Bishop Score ≤ 4. This study was conducted at the Departement of Obstetrics and Gynecology, Dr. M. Djamil Central General Hospital, and Reksodiwiryo Hospital Padang from November 2013 – August 2014 Simple Random Sampling design. The subject selected based on inclusion criteria, then assess the state of the cervix and laboratory examination and nonstress test, then recapitulated and processed data is computerized using the computer software and statistical test. Significant differences increase bishop scores on 25 mcg misoprostol orally with those not given to premature rupture of membranes at term with less than bishop scores or equal to (≤) 4. The p-value evidence this was 0.000 <0.05. And there is no side effects in this study.Keywords: misoprostol effectivity, premature rupture of membrane